Effects of methanol and formic acid on CRYB, ALDH2, and ATP5A1 of RGCs. (3rd July 2022) - Liu, Dongmei; Chen, Jiemin; Xia, Wentao; Zhou, Zhilu; Hao, Hongxia
Abstract: Objective: To explore the toxicity of methanol and its metabolite, formic acid on αB-crystallin(CRYB), aldehyde dehydrogenase (ALDH2), and ATPsynthase (ATP5A1) of rat retinal ganglion cells (RGCs). Methods: RGCs are cultured in vitro in a toxic environment with 15/30/60 mM methanol or formic acid, respectively. Then, the morphological changes of RGCs and protein and mRNA levels of ALDH2, ATP5A1, and CRYB in rat RGCs were evaluated. Results: 1) Compared to the toxicity of 15 mM formic acid on RGCs, 30 mM of formic acid environment significantly promoted apoptosis, and cell death occurred in the 60-mM formic acid group 24 h later. The toxicity of methanol for inducing apoptosis was not as obvious as formic acid. 2) In the 15-mM group, the level of CRYB protein was down-regulated after stimulating with both methanol and formic acid for 48 h, and ATP5A1 protein level decreased significantly with formic but not methanol. No change in ALDH2 was observed in methanol or formic acid. With a prolonged duration (>7 d) or high concentration (>30 mM) stimulation, cells treated with both methanol and formic acid showed severe apoptosis, rendering it challenging to collect a sufficient number of cells for protein detection. 3) In the 48-h group, no significant effect was detected on the mRNA of CRYB, ATP5A1, and ALDH2 by both 15/30 mM formic acid and 15 mM methanol. Conversely, 30 mM methanol had a significant up-regulation effect on the expression of the three genes, while no significant effect was observed in the 7-d groups. Conclusions: Formic acid exerted stronger toxicity on CRYB, ATP5A1, and ALDH2 than methanol and played a regulatory role at the translation level, while the effect of methanol is still uncertain, needing additional investigation.